A Review of National Monitoring Requirements to Support Offshore Carbon Capture and Storage - Turrell, William R.; Berx, Barbara; Bresnan, Eileen; León, Pablo; Rouse, Sally; Webster, Lynda; Walsham, Pamela; Wilson, Jared; Wright, Peter (Frontiers in Marine Science, 2022)
There is an urgent need to reduce global greenhouse gas emissions. One method of achieving this is through Carbon Capture and Storage (CCS). Geological structures that lie offshore under continental shelf seas offer huge CCS storage potential. An emerging marine industry is developing to exploit this potential and national marine monitoring agencies will soon need to consider the potential impacts of this emerging industry. This review of published literature is aimed at generalists responsible for the delivery of national marine monitoring, as well as those involved in the management of the marine environment. It briefly summarizes why the emerging offshore CCS industry is needed, how large it may be and what marine infrastructure may be involved. For the purposes of this paper, a hypothetical 20 Mtpa industry has been used to gauge the potential impact of a developing offshore CCS industry. The probability of CO2 leaks from such an industry is low. If they do occur, the spatial scale of impact will be small, and the potential environmental impacts will be low. Irrespective of how CO2 is transported or stored within shelf seas, leaked CO2 will enter the sea as a gas or as a solution dissolved in sediment pore water. CO2 as a gas will dissolve into seawater and/or directly vent to the atmosphere, depending on the initial conditions of the leak. The most probable source of leaks in a developed CCS industry is from pipelines (currently a 2-year event per 1000 km pipeline). The most probable source of leakage from geological storage is through abandoned wells (a 20- to 80-year event for a 20 Mtpa industry). The source of leaks from a CCS scheme with the potential to release the greatest mass of CO2 is through geological faults, as these may go undetected (if they occur) for long periods. The probability of leaks from geological storage, through faults or abandoned wells, is site dependent and minimized by the site selection process. The review concludes with recommended priorities for future marine science development.